PENGARUH PEMBERIAN EDUKASI PRE-OPERATIF DENGAN PEMUTARAN VIDEO PROSEDUR ANESTESI TERHADAP TINGKAT KECEMASAN PADA PESIEN SPINAL ANESTESI DI IBS RSUD KOLONEL - Arizal (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
According to data, 90% of preoperative patients have the potential to experience anxiety. Patients who experience anxiety when going to surgery and not. If left untreated, it can result in delayed surgery. Another effort to deal with anxiety in patients is by using video playback media for anesthesia procedures.This study aims to determine the effect of providing pre-operative education on the anxiety level of spinal anesthesia patients at Col. Abundjani Merangin.This study uses a quantitative method with a quasy experimental research type with a one group pretest posttest research design. The population and sample were all patients who underwent surgery with spinal anesthesia at IBS Colonel Abundjani Merangin Hospital and the number of samples based on calculations obtained 39 people, the research instrument used the Visual Analoge Scale For Anxiety (VAS-A), and the data analysis used by researchers was the T test.Statistical Test Results There is an Effect of Providing Pre-Operative Education with Video Screening of Anesthesia Procedures on the Level of Anxiety in Spinal Anesthesia Patients at IBS Colonel Abundjani Merangin Hospital (p = 0.000) <0.05.It can be concluded that there is an effect of providing pre-operative education with video screening of anesthesia procedures on the level of anxiety in spinal anesthesia patients at IBS Colonel Abundjani Merangin Hospital. Keywords: Pre-operative Education, Anxiety, Video